Measuring the shock attenuation properties of skateboarding shoes - Determan, J. J.; Frederick, E. C.; Nevitt, M. N. (Footwear Science, 2009)
The development of chronic ankle instability (CAI) is the primary residual deficit after ankle joint sprain. It has been proposed that CAI is characterized by two entities, namely, mechanical instability and functional instability. Each of these entities in turn is composed of various insufficiencies. Research of functional insufficiencies to date has shown large variances in results. One particular reason for this could be discrepancies in inclusion criteria and definitions between CAI, mechanical instability, and functional instability used in the literature. Thus, we endeavored to undertake a systematic investigation of those studies published in the area of CAI to identify if there is a large discrepancy in inclusion criteria across studies.